Daya Interaksi Beberapa Varietas dengan Berbagai Defiensi Air Fase Tumbuh Kedelai [Glycine max (L) Merrill] Berdasarkan Pertumbuhan, Produksi dan Kandungan Prolin - Maisura Maisura; Hendrival Hendrival (Jurnal Agrista, 2007)
The Interaction Water Deficiency Level and Soybean Varieties [Glycine max (L) Merr] Capacity to the Plant Growth, Product and Prolin ContentABSTRACT. The research was conducted to study the interaction water deficiency level and soybean varieties to capacity of the plant growth, product and prolin content. The experiment as factorial experiment in a completely randomized design was applied. The first treatment factors were three level varieties soybean: Kipas putih, Wilis, and Singgalang. The second factor were four level water deficiency: no water deficiency along the growth period, water deficiency along early vegetative growth period, water deficiency along early active of vegetative growth period, water deficiency along flowering, and forming and seed filling period, and water deficiency along seed maturity period. The results showed the water deficiency along each growth period decreased the growth and production. In contrast the water deficiency increases the plant prolin content. The water deficiency along flowering, forming and seed filling period decreased number of pod of all variety. The variety Kipas Putih decreased about 42.49% were compared to the same criteria with no water deficiency in all growth period where water given in normal amount along the through growth period.